Citrus Greening (Huanglongbing; HLB) Blight and Tristeza Comparison Identification Sheet - M. M. Dewdney; J. D. Burrow; L. M. Diepenbrock; R. H. Brlansky; T. M. Spann (EDIS)
This Spanish/English document is a two-page illustrated identification sheet for Citrus Greening that includes a comparison chart for Citrus Greening, Blight and Tristeza.